Dabigatran effects on the international normalized ratio, activated partial thromboplastin time, thrombin time, and fibrinogen: a multicenter, in vitro study - Dager, William E; Gosselin, Robert C; Kitchen, Steve; Dwyre, Dennis (The Annals of pharmacotherapy, 2012)
Patients receiving the direct thrombin inhibitor dabigatran may have selected anticoagulation assays performed as part of routine care. The effect of dabigatran on the international normalized ratio (INR), activated partial thromboplastin time (aPTT), thrombin time (TT), and fibrinogen requires clarification. To describe the effect of dabigatran on selected assays in North America and the United Kingdom. Pooled normal plasma enriched with dabigatran at concentrations of 25, 50, 75, 100, 125, 150, 200, 300, 400, and 500 ng/mL were sent blinded to 19 centers in the US, the UK, and Canada to assess the effect of dabigatran on routine coagulation screening tests, the INR, aPTT, TT, and fibrinogen. Data were returned from 16 centers. For effects on INR, Neoplastine CI Plus and Simplastin HTF were the most sensitive and Thromborel S the least sensitive to increasing dabigatran concentrations. For the aPTT, all reagents demonstrated decreasing sensitivity to increasing dabigatran concentrations. Measured fibrinogen either demonstrated no change or factitious decrease with increasing dabigatran concentrations. Commercial TT methods were very sensitive to low concentrations of dabigatran, with 9 of 10 reporting sites exceeding test limits at dabigatran concentrations of 100 ng/mL. The INR, aPTT, and TT rise as dabigatran concentrations increase. Both the INR and aPTT increase in a linear pattern with marginal slopes, creating challenges in using these assays as reliable means for assessing the amount of dabigatran present. The commercial TT assay is very sensitive at low concentrations of dabigatran. Fibrinogen test results may be either unaffected or lower in the presence of dabigatran.